Spatial analysis of a case of reverse logistics of medicines in community pharmacies in Brazil - a preliminary study - Martins Oliveira, Camila; Pantoja Moreira de Sena, Maria; Sales, Clarisse Andrade; Paula dos Santos Capim, Leiliane de; Nunes Cardoso Mello, Amanda Gabryelle; Fernandes Vieira, Jose Luiz; Mares Azevedo Ribeiro, Carolina Heitmann; Pereira de Sena, Luann Wendel (Pharmacy practice : official journal of the GRIPP (Global Research Institute of Pharmacy Practice), 2023)
Background: The reverse logistics of medicines consists of the logistical procedure of collection, transport, storage, treatment and final disposal of post-consumer or expired waste. Medicines can be toxic to the environment and affect the health of citizens of the territory. Community pharmacies, as a health facility, play a key role in this process. Objectives: Define the spatial analysis and cases of reverse logistics of medicines in community pharmacies in Brazil. Methods: This is a cross-sectional study, and the research covered the medicines collected by 400 community pharmacies in the period from 2020 to 2022. To obtain the data, the medicines were collected, weighed, segregated and the weight released on a dedicated waste management platform. All regions of Brazil subject to georeferencing were processed using the free software Geographic Information System (QGIS). Data were expressed as median and range or as frequency of occurrence. Chi-square t-test and Fisher’s exact test were used to compare variables. The accepted significance level was 5%. Results: Of the five existing regions in Brazil, only three had records of reverse medication logistics. 4,519.74 Kg of products were collected, and the North region of Brazil was responsible for 69.1% of the collection. In the spatial analysis, it was possible to perceive a difference between the areas of concentration of the RDL, that is, locations where collections were carried out in the period from 2020 to 2022. Conclusion: The present study preliminarily analyzed the reverse logistics of medicines in Brazil. The data obtained can contribute to the knowledge of this area and to the strengthening of the process. Thus, these places must exercise a task force for the educational process of the population about the risks of incorrect disposal of medicines and that this could harm the environment, economic aspects of society, food and the entire context that involves health and well-being of citizens.